An Evaluation of Navy En Route Care Training Using a High-Fidelity Medical Simulation Scenario of Interfacility Patient Transport. Issue 9 (14th March 2018) - DeForest, Christine A; Blackman, Virginia; Alex, John E; Reeves, Lauren; Mora, Alejandra; Perez, Crystal; Maddry, Joseph; Selby, Domenique; Walrath, Benjamin
Abstract: Introduction: Military prehospital and en route care (ERC) directly impacts patient morbidity and mortality. Provider knowledge and skills are critical variables in the effectiveness of ERC. No Navy doctrine defines provider choice for patient transport or requires standardized provider training. Frequently, Search and Rescue Medical Technicians (SMTs) and Navy Nurses (ERC RNs) are tasked with this mission though physicians have also been used. Navy ERC provider training varies greatly by professional role. Historically, evaluations of ERC and patient outcomes have been based on retrospective analyses of incomplete data sets that provide limited insight on ERC practices. Little evidence exists to determine if current training is adequate to care for the most common injuries seen in combat trauma patients. Materials and Methods: Simulation technology facilitates a standardized patient encounter to enable complete, prospective data collection while studying provider type as the independent variable. Information acquired through skill performance observation can be used to make evidence-based recommendations to improve ERC training. This IRB approved multi-center study funded through a Congressionally Directed Medical Research Program grant from the Combat Casualty Care Intramural Research Joint En Route Care portfolio evaluated Navy ERC providers. The study evaluated 84 SMT, ERC RN, and physician participants in the performance of critical and secondary actions during an immersive, high-fidelity, patient transport simulation scenario focused on the care during an interfacility transfer. Simulation evaluators with military ERC expertise, blinded to participant training and background, graded each participant's performance. Inter-rater reliability was calculated using Cohen's Kappa to evaluate concordance between evaluator assessments. Categorical data were reported as frequencies and percentages. Performance attempt and accuracy rates were compared with likelihood ratio chi-square or Fisher's exact test where appropriate. Tests were two-tailed and we considered results significant, that is, a difference not likely due to chance exists between groups, if p < 0.05. Confidence intervals were used to present overlap in performance between provider types. Results: Critical and secondary actions were assessed. A majority of providers completed at least one of the critical life-saving actions; only one participant completed all critical actions. Evaluation of critical actions demonstrated that a tourniquet was applied by 64% of providers, blood products administered by 46%, needle decompression performed by 51%, and a complete handoff report performed by 48%. Assessment of secondary actions demonstrated analgesic was accurately administered by 24% of all providers, and 44% reinforced the "hemorrhaging amputation site dressing." Conclusion: Over 98% of participants failed to properly perform all critical actions during the interfacility transfer scenario, which in a real-life combat casualty transport scenario could result in a preventable death. Study results demonstrate serious skill deficits among all types of Navy ERC providers. These data can be used to improve the training of Navy ERC providers, ultimately improving care to injured soldiers, sailors, airmen, and marines.